Japan quality control circles: quality control circle case studies - Asian Productivity Organization (Tokyo: Asian Productivity Organisation, 1972)
This book consists of a series of articles translated from Factory Management magazine Tokyo. It includes five introductory articles written by managerial personal and 18 case studies written by the production workers themselves. It is directed mainly to the QC circle leaders and members.
The advancing QC circle movement -- The QC circle and human relationships -- QC circle activities and implementation of QC techniques -- The QC circle and training -- Smaller enterprises and QC circle activities -- Eliminating machining errors -- Reduction of dimensional defects in felt -- Rewind cutting process improved -- Reduction of defects in metal plates -- Reducing refrigerator component processing defects -- Simplification of the weighing of rubber compounding ingredients -- Replacement of intermediate inspection by independent inspection -- Reduction of raw silk sticking -- Reduction of defective soldering work in assembling electrical appliances -- Taking the leadership in quality control -- Early operation of newly installed machinery -- Increasing efficiency by improving operation methods -- Improvement of the operating rate of synthetic yarn spinning -- Providing incentives to the QC circle through an evaluation system -- Reduction in deflection of gear shafts -- Improvement in cylinder bore smoothness -- The QC circle movement (applied to shop requirements) -- Elimination of inspection in the 'A' packing process
Keywords: Statistics -- Quality control